2010
DOI: 10.1002/lary.20879
|View full text |Cite
|
Sign up to set email alerts
|

The use of the “puffed‐cheek” computed tomography technique to confirm the diagnosis of pneumoparotitis

Abstract: Pneumoparotitis is a rare etiology of symptomatic parotid gland enlargement that is often misdiagnosed clinically. Pneumoparotitis results from air refluxing into the parotid ductal system via an incompetent Stensen duct orifice. We report a protracted case of pneumoparotitis evaluated with the "puffed-cheek" computed tomography technique to help confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
1
9
1
Order By: Relevance
“…The gold standard for diagnosing pneumoparotitis is computed tomography, which reliably identifies air in the ductal system and is useful for differentiating air from calculi and inflammation [3,6]. Recent studies have suggested that a “puffed cheek” computed tomography technique has the potential to aid in diagnosis and reveal a greater prevalence [6]. Ultrasound is also useful for diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gold standard for diagnosing pneumoparotitis is computed tomography, which reliably identifies air in the ductal system and is useful for differentiating air from calculi and inflammation [3,6]. Recent studies have suggested that a “puffed cheek” computed tomography technique has the potential to aid in diagnosis and reveal a greater prevalence [6]. Ultrasound is also useful for diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a “puffed cheek” computed tomography technique has the potential to aid in diagnosis and reveal a greater prevalence [6]. Ultrasound is also useful for diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated episodes of pneumoparotid may cause to chronic inflammation, infection or sialectasis. The pathophysiologic condition of pneumoparotid has also been demonstrated by using a "puffed-cheek" technique [53], usually performed a CT examination after sialography, which mark filling defects, air in the parotid ductal system and sialoliths. Next, massaging the both patient's parotid glands, CT scan is performed highlighted a reduced amount of air and absence of contrast.…”
mentioning
confidence: 99%
“…Currently, CT is the gold-standard technique because it defines anatomy and it is not invasive.Describing air-filled dilatation of Stensen's duct, glandular acini air dilatation, collections, free air intraparenchymal and a good imaging of duct glandular system, also helps in diagnoses of extension of air-accumulation in the nearest areas of the head-neck district [2]. Puffed-cheek CT is a good technique that demonstrated a subtle, but definite increase in intraductual and intraglandular parotid air when is compared to the simple CT [53].…”
mentioning
confidence: 99%
“…The visualization of small sialoliths can be further improved by hyperflexion of the neck, which eliminates artifacts due to dental restorations (Figure 1). The puffed-cheek technique recently has been reported to be effective in the radiologic diagnosis of pneumoparotitis [8]. The surfaces of the oral cavity that are often in contact are the buccal (cheek) mucosa more posteriorly or the labial (lip) mucosa more anteriorly, and the alveolar (gingival) mucosa of the mandible and maxilla.…”
Section: Parotid Spacementioning
confidence: 99%